Mismatched menu: the incompatibility of adult black soldier flies as praying mantis feed - Klüber, Patrick; Gabche, Raissa (Frontiers in Insect Science, 2025)
Praying mantises are known for their striking predatory behavior and are becoming increasingly popular with hobbyists and for scientific research. As generalist predators with a wide range of insect-based diets, it is crucial to identify suitable prey options, especially for restricted environments such as terrariums, which are limited compared to the wild. This study investigates the use of adult black soldier flies (BSF; Hermetia illucens; Linnaeus, 1758) as a sole food source for two mantis species, Chlidonoptera lestoni (Roy & Leston, 1975) and Hierodula patellifera (Serville, 1839), while assessing their suitability and potential challenges associated with their digestion. The BSF is widely recognized for its high nutritional value and ease of rearing, making it an attractive prey candidate for mantises. Although natural capture behavior and high feed acceptance have been observed, adult BSF seem not to be suitable as sole feed for both mantises. Our results suggest that imbalances in macronutrients, particularly the protein/fat ratio, may contribute to high mortality. The use of BSF as a mono-diet could also limit access to a variety of beneficial microorganisms that are essential for maintaining a healthy gut microbiota in mantises, thereby affecting their immunity and well-being in captivity. In addition, the possible presence of pathogenic microorganisms in the BSF could also have affected the mantises’ survival. Future studies should focus on the nutritional adjustment of BSF, as their chemical composition is strongly dependent on the feed they are reared on.